Rancang Bangun Kompor Biomassa sebagai Kompor Ramah Lingkungan - Nanda Eka Putra; Aris Fiatno; Novi Yona Sidratul Munti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
This study aims to design an environmentally friendly biomass stove and make an environmentally friendly biomass stove. To calculate the cooking time using a biomass stove and to compare the time required on a biomass stove with a gas stove. The benefits for researchers are that they can make stoves that are competitive with gas or electric fuel stoves so that they become an alternative for the community and make biomass stoves one of the MSME products in the region. The type of research used in this study uses a qualitative research method with interview techniques. Informants or respondents in this study are housewives. The mothers were chosen because they were considered more experienced in cooking using the stove. From the research conducted, it is concluded that the results of the design of the biomass stove as an environmentally friendly stove, this biomass stove is able to reduce the carbon footprint because it produces fewer carbon emissions compared to fossil fuels. Reducing the amount of methane in the atmosphere because by using biomass, the amount of methane in the atmosphere can be reduced. Biomass stoves are stoves that are capable of making recycled fuel. This is a huge advantage as it means that no industrial output is wasted. All waste products from industry can be used to produce biomass energy.